Derivation and validation of a scoring system to predict after discharge risk of cardiac events in patients with acute myocardial infarction undergoing percutaneous coronary revascularization. (25th November 2020) - Corsini, A; Massarelli, G; Bruno, M; Bruno, A.G; Compagnone, M; Ghetti, G; Saia, F; Galie', N; Taglieri, N
Abstract: Background: In the acute coronary syndromes (ACS) setting, despite the extensive use of coronary revascularization and P2Y12 inhibitors such as prasugrel and ticagrelor, with a more pronounced inhibitory effect on platelets than clopidogrel, the rate of death and recurrent myocardial infarction (MI) at 1 year is still high. In this clinical setting the development of a risk score which takes into account patient's and procedural characteristics could represent a useful tool to identify patients at high risk for ischaemic events at 1 year who could take advantage from more aggressive secondary prevention strategies. Purpose: The aim of our study was to develop a risk score to predict 1-year probability of after discharge cardiac events (recurrent MI and cardiac death) in patients with acute MI treated with percutaneous coronary intervention (PCI). Methods: We prospectively enrolled all consecutive patients hospitalized for acute MI between 2003 and 2017 treated with PCI with/without stent placement at our center. We excluded patients who died in-hospital or who experienced in-hospital recurrent MI and patients undergoing surgical revascularization by coronary artery bypass graft (CABG). The patients of the final study cohort were therefore randomly assigned to either a derivation sample (60%) or a validation sample (40%). Based on the multivariate analysis we developed a point system according to the "Framingham Risk Score" method. Results: The final study cohort, represented by 4922 patients, was split in a derivation sample of 2972 patients and in a validation sample of 1950 patients: in both groups the median age was around 70 years; the male prevalence was 73%; 65% of patients were dagnosed with ST-segment elevation MI. The clinical prediction score underlined as risk factors for recurrent cardiac events older age, diabetes mellitus, peripheral arterial disease, prior MI, Killip class >2 at presentation, higher platelet count and creatinine values, lower left ventricular ejection fraction; radial access and the use of second generation drug eluting stents resulted to be protective. This model showed a good discrimination power in both the derivation and the validation samples with an area under the curve (AUC) of 0.75 and 0.71, respectively. The calibration showed a good concordance between predicted and observed events in both the derivation and the validation samples. Same results were observed in patients with/without ST-segment elevation MI and in gender subgroups. Conclusions: The present study, conducted retrospectively on a large population of patients with acute MI treated with PCI enrolled prospectively, enabled us to derivate and validate a risk score of cardiac death and recurrent MI at 1 year which took into account both clinical and procedural characteristics and which demonstrated a good predictive performance. Funding Acknowledgement: Type of funding source: None